PENGALAMAN PELANGGAN, ULASAN PELANGGAN SECARA DARING, DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG - Rahmandika, Muhammad Daffa; Rohman, Factur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine and analyze the influence of customer experience, online customer reviews and product variations on Traveloka consumers' Repurchasing decisions. The sample in this study amounted to 106 respondents who are Traveloka customers at Brawijaya University Malang City with a minimum of one transaction. The sampling technique is non-probability sampling using convenience sampling. Data were collected using questionnaires, literature study and internet browsing. The data analysis technique used SPSS 25. The data were then analyzed by multiple regression analysis. The results showed that partially customer experience, online customer reviews and product variations had a positive and significant effect on repurchasing decisions. The results of this study indicate that customer experience, online customer reviews and product variations have a positive and significant effect on repurchasing decisions. The coefficient of determination adjusted r square is 0.867, which means that the variable customer experience, online customer reviews and product variations are able to influence repurchasing decisions by 86.7% while the remaining 13.3% is influenced by other variables not examined in this study.